Chronology of tectonic, geomorphic, and volcanic interactions and the tempo of fault slip near Little Lake, California - Amos,CB; Brownlee,SJ; Rood,DH; Burch,Fisher G; Bürgmann,R; Renne,PR; Jayko,AS (Bulletin of the Geological Society of America, 2013)
New geochronologic and geomorphic constraints on the Little Lake fault in the Eastern California shear zone reveal steady, modest rates of dextral slip during and since the midto-late Pleistocene. We focus on a suite of offset fluvial landforms in the Pleistocene Owens River channel that formed in response to peri odic interaction with nearby basalt flows, thereby recording displacement over multiple time intervals. Overlap between 40Ar/39Ar ages for the youngest intracanyon basalt flow and 10Be surface exposure dating of downstream terrace surfaces suggests widespread channel incision during a prominent outburst flood through the Little Lake channel at ca. 64 ka. Older basalt flows flanking the upper and lower canyon margins indicate localization of the Owens River in its current position between 212 ± 14 and 197 ± 11 ka. Coupled with terrestrial light detection and ranging (lidar) and digital topographic measurements of dextral offset, the revised Little Lake chronology indicates average dextral slip rates of at least ~0.6-0.7 mm/yr and <1.3 mm/yr over intervals ranging from ~104 to 105 yr. Despite previous geodetic observations of relatively rapid interseismic strain along the Little Lake fault, we find no evidence for sustained temporal fluctuations in slip rates over multiple earthquake cycles. Instead, our results indicate that accelerated fault loading may be transient over much shorter periods (~101 yr) and perhaps indicative of time-dependent seismic hazard associated with Eastern California shear zone faults. © 2013 Geological Society of America.